A second generation of RT-PCR assay for detection of human immunodeficiency virus type 1 (HIV-1) infection (Medical Journal of Indonesia, 2010)
Aim A spesific and rapid diagnosis such as RT-PCR assay is the most needed to minimize transmission of HIV-1 infection. Therefore, in this study we developed the RT-PCR assay that was spesific against the gag gene of HIV-1. Methods The developed RT-PCR assay was evaluated against 46 specimens that were obtained from voluntary counseling and testing for HIV (VCT) in Rumah Sakit Umum Pemerintah (RSUP) Sanglah, Bali. To get the sensitivity and specificity of RT-PCR assay, the results of assays were compared with the results of commercially serologic teststhat were commonly used in Indonesia. Results The RT-PCR assay could detect 21 of 26 serologic test-positive specimens and showed 19 negative results of 20 serologic test-negative specimens. There was one specimen that was positive in RT-PCR but negative in serologic assay, which might depict a true yield at particular condition when the serologic assay was unable to detect. Five serologic positive-test specimens were negative by RT-PCR that was possibly caused by low detection level of the assay. Conclusion The RT-PCR assay is potential to be used for the detection of HIV-1 infection with a sensitivity and specificity of 80.8% and 95.0% respectively. (Med J Indones 2010;19:154-7)